Public Acceptance on Hypnotheraphy as a Complementary Alternative Health Service - Adi W. Gunawan; Muhadjir Darwin; Kwartarini Wahyu Yuniarti; Yodi Mahendradhata (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
Despite the pros and cons, the practice of hypnotherapy is growing in Indonesia. How are the hypnotherapy clients aware about hypnotherapy? Is the process of acceptance in line with the pattern of adoption of the innovation? Theoretically, there are five stages of the process of adoption of an innovation: awareness, interest, evaluation, first-trial, and confirmation. This study was conducted in four major cities in Java. A sequential-explanatory mixed method was applied. There were two stages for this method, quantitative survey and then followed by qualitative study. The conclusion suggested that the acceptance of hypnotherapy by clients depended on its effectiveness in helping them to cope with their problems. The finding also corroborated and slightly added to the five-stages theory of the process of innovation adoption. The most effective communication channel in the process of adopting hypnotherapy was face-to-face and interpersonal, with the hypnotherapy clients as diffusion agents. The most important message in the context of developing the hypnotherapist profession was that hypnotherapy is an evidence-based professional service.